2006
DOI: 10.1097/01.pcc.0000235245.49129.27
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and early predictive factors of mortality and outcome in children with traumatic severe brain injury: Experience of a French pediatric trauma center*

Abstract: Initial hypotension, Glasgow Coma Scale, and Injury Severity Score are independent predictors of outcome in children with traumatic brain injury. Threshold values can be calculated for predicting poor outcome. These variables can be easily and detected early in this population and used for quality assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
6
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(131 citation statements)
references
References 43 publications
7
104
6
10
Order By: Relevance
“…[14] More than 30% of these deaths can be prevented by quality primary treatment. [15] Quantitative trauma scoring systems are important methods of evaluating and comparing trauma treatment standards. [16] Males comprised the majority of the present population, in accordance with the findings of others.…”
Section: Discussionmentioning
confidence: 99%
“…[14] More than 30% of these deaths can be prevented by quality primary treatment. [15] Quantitative trauma scoring systems are important methods of evaluating and comparing trauma treatment standards. [16] Males comprised the majority of the present population, in accordance with the findings of others.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary insults, representing discrete events that may be monitored for and intervened upon, are predictable, potentially avoidable, and include systemic causes such as hypotension [93,94], hypocarbia, hypercarbia [78,79,95], hypoxia [11,96], hyperthermia [97], and hyperglycemia [98,99]. These insults result in secondary injuries which signify underlying neurological processes related to cellular and molecular mechanisms of injury/ death, including inflammatory responses, impairment of cerebral autoregulation, excitotoxicity, delayed cell death, and BBB breakdown [92].…”
Section: Secondary Insults and Injuriesmentioning
confidence: 99%
“…For preverbal children, the pediatric coma scale is preferred. 25 In a large series of pediatric severe TBI, Ducrocq et al 9 reported that a threshold GCS score of 5 or less was associated with mortality and poor outcome. In our study, initial GCS demonstrated an association with different measures of CPP and PbtO 2 .…”
Section: Glasgow Coma Scalementioning
confidence: 99%
“…3,6,9,16 Given that sedation in the acute phase may influence 2 components of the GCS, (eye opening and verbal responses), the motor component of the GCS is often considered to represent a more reliable assessment. For preverbal children, the pediatric coma scale is preferred.…”
Section: Glasgow Coma Scalementioning
confidence: 99%
See 1 more Smart Citation